2015
DOI: 10.1155/2015/928385
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Bone Health in Duchenne Muscular Dystrophy

Abstract: Duchenne muscular dystrophy (DMD) is an X-linked recessive disorder characterized by progressive muscle weakness, with eventual loss of ambulation and premature death. The approved therapy with corticosteroids improves muscle strength, prolongs ambulation, and maintains pulmonary function. However, the osteoporotic impact of chronic corticosteroid use further impairs the underlying reduced bone mass seen in DMD, leading to increased fragility fractures of long bones and vertebrae. These serious sequelae advers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 66 publications
0
38
0
3
Order By: Relevance
“…It is characterized by severe and persistent muscle weakness and loss of muscle mass, leading to immobility and long-term corticosteroid use is an approved and proven treatment[62]. A tendency toward obesity emerges by early adolescence; a cohort study of 252 steroid-naïve boys reported obesity in up to 54% of participants, followed by a decline in obesity in late adolescence[63].…”
Section: Clinical Considerations In the Evaluation Of Bone Health In mentioning
confidence: 99%
See 1 more Smart Citation
“…It is characterized by severe and persistent muscle weakness and loss of muscle mass, leading to immobility and long-term corticosteroid use is an approved and proven treatment[62]. A tendency toward obesity emerges by early adolescence; a cohort study of 252 steroid-naïve boys reported obesity in up to 54% of participants, followed by a decline in obesity in late adolescence[63].…”
Section: Clinical Considerations In the Evaluation Of Bone Health In mentioning
confidence: 99%
“…A tendency toward obesity emerges by early adolescence; a cohort study of 252 steroid-naïve boys reported obesity in up to 54% of participants, followed by a decline in obesity in late adolescence[63]. Several prior studies have described deficiencies in aBMD in this population along with marked increase in fragility fractures[62, 64, 65]. These observed patterns in bone outcomes are due, to some degree, to immobility.…”
Section: Clinical Considerations In the Evaluation Of Bone Health In mentioning
confidence: 99%
“…Limited published data exist on the use of BPs for GIO in children. GIO is prevalent in children with Duchene muscular dystrophy treated with long term GCs and many studies have reported positive outcome (28,29). It is important to note that there is potential for recovery of bone density with reduced fracture risk to expected for age in children once GCs are discontinued (30,31).…”
Section: Steroids-induced Osteoporosismentioning
confidence: 99%
“…Duchenne muscular dystrophy is characterized by progressive muscle weakness, ambulation loss and premature death 3 . The lack of dystrophin results in degeneration of muscle fibers, which are replaced by fat and connective tissue 1 .…”
mentioning
confidence: 99%